Методологічні засади визначення об'єму втрат природного газу та мінімізації його дисбалансів в системах транспортування та розподілу - Матіко, Федір Дмитрович (Національний університет "Львівська політехніка", 2015)
У дисертації розв’язано важливу науково-прикладну проблему - розроблення науково-обґрунтованих методів визначення об’єму втрат природного газу та зменшення дисбалансу об’єму газу в газотранспортних та газорозподільних системах. Сформовано методологічні засади визначення дисбалансу об’єму газу, як комплексного показника, який визначається систематичними та методичними похибками визначення об’єму газу. Розроблено математичні моделі для визначення основних систематичних та методичних похибок вимірювання об’єму газу за допомогою лічильників та витратомірів змінного перепаду тиску, розроблено способи їх зменшення, удосконалені вимоги до конструктивного виконання систем обліку газу. Розроблено нові більш точні рівняння і методики визначення фізичних властивостей природного газу. Впроваджено розроблені способи та методики у нормативні документи, що дозволило реалізувати їх під час виробництва та застосування приладів обліку газу і зменшити втрати газу, зумовлені похибками вимірювання об’єму газу. Розроблено методологію нормування технологічних витрат та втрат газу, яка передбачає застосування удосконалених у роботі математичних моделей та методів вимірювання об’єму втрат газу, що дозволило удосконалити нормативні документи з визначення технологічних витрат та втрат газу в газорозподільних мережах та зменшити об’єм втрат газу. Основні результати роботи впроваджено у газотранспортних та газорозподільних організаціях, підприємствах виробниках засобів обліку та підрозділах Держспоживстандарту України. В диссертации решена важная научно-прикладная проблема - разработка научно-обоснованных методов определения объема потерь природного газа и уменьшения дисбаланса объема газа в газотранспортных и газораспределительных системах. Сформированы методологические основы определения дисбаланса объема газа, как комплексного показателя, который определяется систематическими и методическими погрешностями определения объема газа. Разработаны математические модели для определения основных систематических и методических погрешностей измерения объема газа с помощью счетчиков и расходомеров переменного перепада давления, разработаны способы их уменьшения, усовершенствованы требования к конструктивному исполнению систем учета газа. Разработаны новые более точные уравнения и методики определения физических свойств природного газа. Разработанные способы и методики внедрены в нормативные документы, что позволило реализовать их во время производства и применения приборов учета газа и уменьшить потери газа, обусловленные погрешностями измерения объема газа. Разработана методология нормирования технологических расходов и потерь газа, которая предусматривает применение полученных в работе математических моделей и методов измерения объема потерь газа, что позволило усовершенствовать нормативные документы по определению технологических расходов и потерь газа в газораспределительных сетях и уменьшить объем потерь газа. Основе результаты работы внедрены в газотранспортных и газораспределительных организациях, в производстве средств учета и в подразделениях Госпотребстандарта Украины. The dissertation work is devoted to important scientific and applied problem - development of scientific methods of determination of volume of natural gas losses and reducing imbalances of gas volume in gas transmission and distribution systems. In this work it was analyzed the possible causes of imbalances of gas volume and proved that imbalance of gas volume is the complex parameter which depends on systematic and methodical errors of determination of the volume of gas supplied to the gas pipeline system or taken from it. Application of the concept of imbalance enabled to develop the theoretical basis for determination of the imbalance in the gas transmission or gas distribution systems and evaluation its limit values. Methodological principles are developed in order to choose metering instrumentation by criterion of minimizing the absolute uncertainty of the measured gas volume. They provide the possibility to minimize the imbalance of gas volume in gas transmission and distribution systems. The additional systematic, unexcluded systematic and methodical errors of measurement of gas volume using gas meters and pressure differential flowmeters are analyzed. New analytical dependences of the main error of rotary gas meters from the accounted gas volume are developed. These equations provide the possibility to define the change of the main error of gas meter during its exploitation and the necessity of its extraordinary verification. New technique is developed for reduction of gas losses caused by using of the household gas meters without means of conversion of gas volume to base conditions. The method for calibration of the gas meters according to the average annual gas temperature and pressure weighed by the consumed gas volumes is realized. Applying the results of studies of additional systematic error of measurement of gas temperature it was obtained a new mathematical model of additional systematic error of measurement of gas volume caused by additional error of measurement of gas temperature. This model provides the possibility to create design requirements for gas metering systems depending on their using conditions. The detected unexcluded systematic errors of coefficients of flowrate equation of pressure differential flowmeters are analyzed at working conditions at the inputs and outputs of gas transmission and distribution systems. Methodological principles of reduction of imbalances of gas volume are developed by minimization of unexcluded systematic error of pressure differential flowmeters. The results of their implementation in the gas transmission system UMG "Lvivtransgas" are presented. Based on research results of systematic and methodological errors of measurement of gas volume it was improved the existing normative base. Particularly the technique for calibration and extraordinary verification of gas meters is developed. Some principles of standards set DSTU GOST 8.586.1-5:2009 are developed which enable the reduction of the systematic and methodical errors of measurement of gas volume and consequently the volume of gas imbalances. New equations for isentropic factor, dynamic viscosity, throttling factor of natural gas are obtained which enable to calculate the value of these parameters using simplified data about the gas composition for the extended range of gas pressure. The techniques of service of standard reference data of Ukraine DSSDD 4-2002, DSSDD 8-2006, DSSDD 9¬2006 and interstate service of standard reference data SD 9-2005, SD 14-2008, SD 13¬2008 are developed based on the equations. These techniques provide the reduction of unexcluded systematic error of determination of these parameters and thus improve the accuracy of measurement of gas volume. Mathematical models for determination of the volume of technological expenses and gas losses are improved. Methods for measurement of losses volume caused by leakage of distribution systems are developed. Methodological principles of standardization of technological expenses and gas losses in gas distribution systems are developed which provide using improved mathematical models and methods for determination of the limit values of gas losses from the equipment of gas distribution systems. This enabled to improve normative documents on determination of technological expenses and gas losses in gas distribution systems. Mathematical models of stationary movement of natural gas in pipelines are improved that enables to increase the accuracy of determination of gas volume in pipelines of complex configuration. Based on the mathematical models it was improved the method for determination of gas volume in the main gas pipelines.
Методологические основы определения объема потерь природного газа и минимизации его дисбалансов в системах транспортировки и распределения
Methodological bases principles for determining of volume of natural gas losses and minimize its imbalances in transmission and distribution systems
Keywords: баланс обє'му газу; втрати газу; систематична похибка; лічильник газу; витратомір змінного перепаду тиску; математична модель; фізичні властивості газу; нормування втрат; баланс объема газа; потери газа; систиматическая погрешность; счетчик газа; расходомер переменного перепада давления; математическая модель; физические свойства газа; нормирование потерь; balance of gas volume; gas losses; systematic error; gas meter; pressure differential flowmeter; mathematical model; physical properties of gas; standardization of losses